Microfluidic-templated cell-laden microgels fabricated using phototriggered imine-crosslinking as injectable and adaptable granular gels for bone regeneration. (February 2023) - An, Chuanfeng; Zhou, Renjie; Zhang, Haoyue; Zhang, Yujie; Liu, Weijian; Liu, Jia; Bao, Bingkun; Sun, Kai; Ren, Changle; Zhang, Yang; Lin, Qiuning; Zhang, Lijun; et al.
Abstract: Injectable granular gels consisting of densely packed microgels serving as scaffolding biomaterial have recently shown great potential for applications in tissue regeneration, which allow administration via minimally invasive surgery, on-target cargo delivery, and high efficiency in nutrient/waste exchange. However, limitations such as insufficient mechanical strength, structural integrity, and uncontrollable differentiation of the encapsulated cells in the scaffolds hamper their further applications in the biomedical field. Herein, we developed a new class of granular gels via bottom-up assembly of cell-laden microgels via photo-triggered imine-crosslinking (PIC) chemistry based on the microfluidic technique. The particulate nature of the granular gels rendered them with shear-thinning and self-healing behavior, thereby functioning as an injectable and adaptable cellularized scaffold for bone tissue regeneration. Specifically, single cell-laden, monodisperse microgels composed of methacrylate- and o-nitrobenzene-functionalized hyaluronic acid and gelatin were prepared using a high-throughput microfluidic technique with a production rate up to 3.7 × 10 8 microgels/hr, wherein the PIC chemistry alleviated the oxygen inhibition on free-radical polymerization and facilitated enhanced fabrication accuracy, accelerated gelation rate, and improved network strength. Further in vitro and in vivo studies demonstrated that the microgels can serve as carriers to support the activity of the encapsulated mesenchymal stem cells; these cell-laden microgels can also be used as cellularized bone fillers to induce the regeneration of bone tissues as evidenced by the in vivo experiment using the rat femoral condyle defect model. In general, these results represent a significant step toward the precise fabrication of engineered tissue mimics with single-cell resolution and high cell-density and can potentially offer a powerful tool for the design and applications of a next generation of tissue engineering strategy. Statement of significance: Using microfluidic droplet-based technology, we hereby developed a new class of injectable and moldable granular gels via bottom-up assembly of cell-laden microgels as a versatile platform for tissue regeneration. Phototriggered imine-crosslinking chemistry was introduced for microgel cross-linkage, which allowed for the fabrication of microgels with improved matrix homogeneity, accelerated gelation process, and enhanced mechanical strength. We demonstrated that the microgel building blocks within the granular gels facilitated the proliferation and differentiation of the encapsulated mesenchymal stem cells, which can further serve as a cellularized scaffold for the treatment of bone defects. Graphical abstract: Image, graphical abstract